Virtual Reality (VR) & Augmented Reality (AR) technologies for tourism and hospitality industry - Nayyar, Anand; Mahapatra, Bandana; Nhuong Le, Dac; Suseendran, G (International Journal of Engineering and Technology, 2018)
Virtual Reality and Augmented Reality, these days, is offering many useful applications that is attracting greater attention from tourism researchers and professionals. As, AR and VR technologies are evolving, the number of scientific applications is also at increase. VR and AR are proving their worth especially when planning, marketing, education, tourist sport preservation coming to light. The aim of this research paper is to highlight top technologies for Tourism and Hospitality with regard to AR and VR.Â